Microstructure and mechanical properties of a medium manganese steel treated with interrupted quenching and intercritical annealing. (September 2016) - Tsuchiyama, Toshihiro; Inoue, Taishi; Tobata, Junya; Akama, Daichi; Takaki, Setsuo
Abstract: An Fe-5Mn-0.1C alloy was subjected to interrupted quenching, which involves quenching to a temperature between the martensite start temperature (Ms ) and finish temperature (Mf ), and subsequent intercritical annealing. This resulted in the formation of a unique multi-phase structure consisting of tempered martensite, two types of retained austenite, namely granular and film-like, and fresh martensite. The film-like austenite was observed in the area swept by the untransformed austenite/tempered martensite interface, which is formed during intercritical annealing. Tensile testing revealed that the fresh martensite was effective for increasing the strength, whilst adequate ductility was achieved owing to the transformation-induced plasticity (TRIP) effect. Graphical abstract: